Analysis of Conflicts in Talent Resource Allocation within the Education-Industry Integration of Independent Colleges - Wang, Anna; Qian, Chengjiang; Wang, Xiaoqing (Journal of Educational Research and Policies, 2025)
This paper examines resource allocation conflicts in independent colleges’ integration of production and education, using the conflict analysis graph model (GMCR) to propose solutions. It constructs a four-helix model involving government, industry associations, enterprises, and colleges, analyzing strategic choices and preferences. Using AHP and expert scoring, it evaluates decision weights and finds equilibrium solutions. The study reveals multiple solutions in GMR and SMR, but only one in Nash and SEQ, where all parties actively participate in the integration of industry and education, forming a conducive environment and supporting talent training systems. The paper innovates by applying GMCR to resource conflicts but acknowledges limitations due to reliance on theory and expert scores rather than operational data. Future research should explore model application in real-world scenarios.